Analysis of Long‐Term GIC Measurements in Transformers in Austria. Issue 1 (24th January 2022) - Albert, D.; Schachinger, P.; Bailey, R. L.; Renner, H.; Achleitner, G.
Abstract: Geomagnetically induced currents (GICs), a result of solar wind interaction with the Earth's magnetic field and the resistive ground, are known to flow in power transmission grids, where they can lead to transformer damage and grid operation problems. In this study we present an analysis of five years of continuous GIC measurements in transformer neutral points in Austria. Seven self‐designed stand‐alone measurement systems are currently installed in the Austrian 220 and 380 kV transmission levels, measuring currents up to 25 A. We identify recurrent geomagnetic activity in the measurements, and also find man‐made sources of low frequency currents using frequency analysis. In order to support the transmission grid operators, two GIC simulation approaches are used to simulate GICs in the power grid. The first model uses measurements to derive the sensitivity of the location to northward and eastward geoelectric field components (which requires no detailed grid data), and the second model uses the detailed grid model to compute GICs from a geoelectric field. We evaluate two geomagnetic storms from September 2017 and May 2021 to discuss the effects of GICs on the power transmission grid and its assets. Plain Language Summary: During geomagnetic storms, rapid changes in the Earth's magnetic field induce an electric field in the ground, may drive currents in the power grid. These are called geomagnetically induced currents (GICs) and they can lead to power grid operation problems and even transformer damage. In this study we present learning's from five years of GIC measurements in Austria, which have been carried out in seven different transformers in the grid. Some power grid transformers show larger susceptibility than other transformers to magnetic field variations accompanied by larger GICs. We also identify some of the sources of noise in the data such as a city subway system, and investigate two geomagnetic storms from September 2017 and May 2021 in more detail. Key Points: Measurements of geomagnetically induced currents (GICs) in power grid substation transformers have been carried out since September 2016 in Austria We summarize the measurements until now and discuss data quality and sources of noise A statistical analysis of GIC measurements, a comparison of simulation models for two storms and an attempt to a risk assessment is performed